2011
DOI: 10.1002/dc.21784
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear characteristics of the endometrial cytology: Liquid‐based versus conventional preparation

Abstract: The aim of this study was to assess the utility of liquid-based cytologic preparation (LP) compared with conventional preparation (CP) for the assessment of nuclear findings in endometrial glandular and stromal breakdown (EGBD) which may be misdiagnosed as carcinoma in EGBD cases. The material consists of cytologic smears including 20 cases of proliferative endometrium (PE), 20 cases of EGBD, and 20 cases of endometrioid adenocarcinoma grade1 (G1) for which histopathological diagnosis was obtained by endometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…However, the nuclear shape features appear to be more useful in the discrimination between EGBD and G1 on LBPs. In the differential assessment of nuclear features in LBP versus conventional cytologic preparation (CCP) in EGBD cases, considering the spindle shape of the nucleus, only MCIP showed significantly higher values in LBP than in CCP, and as for the reniform shape of the nucleus, only CCSC showed significantly higher values in LBP compared with CCP [59]. …”
Section: Endometrial Glandular and Stromal Breakdownmentioning
confidence: 99%
“…However, the nuclear shape features appear to be more useful in the discrimination between EGBD and G1 on LBPs. In the differential assessment of nuclear features in LBP versus conventional cytologic preparation (CCP) in EGBD cases, considering the spindle shape of the nucleus, only MCIP showed significantly higher values in LBP than in CCP, and as for the reniform shape of the nucleus, only CCSC showed significantly higher values in LBP compared with CCP [59]. …”
Section: Endometrial Glandular and Stromal Breakdownmentioning
confidence: 99%
“…Endometrial cytology using liquid-based preparation (LP) of specimens has been reported. [11][12][13] We have also reported that the inadequate specimen rate of LP is lower than that of the CP method. 14 Regarding the diagnostic system in endometrial cytology, traditionally, a "three-tier reporting (TTR) system," which consists of "negative," "suspicious positive," and "positive" categories, has been widely used.…”
Section: Introductionmentioning
confidence: 86%
“…Endometrial cytology using liquid‐based preparation (LP) of specimens has been reported . We have also reported that the inadequate specimen rate of LP is lower than that of the CP method .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the clear cytological specimens obtained by the automated processing system in the limited field of glass slides. In the field of endometrial cytology, LBP has started to be utilized for detecting endometrial neoplasia [14,15,16,17,18,19,20]. However, endometrial phasing using LBP specimens has not yet been analyzed, and the results obtained with this method may differ from the knowledge acquired using conventional specimens.…”
Section: Introductionmentioning
confidence: 99%